Integrated Groundwater Management 2016
DOI: 10.1007/978-3-319-23576-9_2
|View full text |Cite
|
Sign up to set email alerts
|

The International Scale of the Groundwater Issue

Abstract: Throughout history, and throughout the world, groundwater has been a major source of water for sustaining human life. Use of this resource has increased dramatically over the last century. In many areas of the world, the balance between human and ecosystem needs is difficult to maintain. Understanding the international scale of the groundwater issue requires metrics and analysis at a commensurate scale. Advances in remote sensing supplement older traditional direct measurement methods for understanding the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Situating findings from this analysis with reference to academic literature revealed limited research addressing rates of groundwater use for drinking, with available figures often presented as background information rather than empirical findings. The overall proportion of the aggregated population from case study countries found to be using groundwater for drinking (79%) is higher than figures reported in the literature, which estimate half of the global population to be reliant on groundwater for drinking [2,5,6,84]. Regional studies estimate that a third of all people in Asia rely on groundwater for drinking [85,86].…”
Section: Data Gaps and Monitoringmentioning
confidence: 87%
“…Situating findings from this analysis with reference to academic literature revealed limited research addressing rates of groundwater use for drinking, with available figures often presented as background information rather than empirical findings. The overall proportion of the aggregated population from case study countries found to be using groundwater for drinking (79%) is higher than figures reported in the literature, which estimate half of the global population to be reliant on groundwater for drinking [2,5,6,84]. Regional studies estimate that a third of all people in Asia rely on groundwater for drinking [85,86].…”
Section: Data Gaps and Monitoringmentioning
confidence: 87%
“…When conducted on working agricultural lands, MAR risks mobilizing nutrients and increasing chemical constituent loading to streams and riparian soils [20,[69][70][71]. MAR can also facilitate groundwater contamination via crop-mediated aquifer contamination of fertilizers and pesticides [72]. Whereas aquifer recharge may introduce water quality concerns elsewhere, return flow from the ESPA is of high quality that is suitable for instream habitat uses [73].…”
Section: Physical and Administrative Mar Implications For Idaho And Hmentioning
confidence: 99%
“…Groundwater is the primary natural water storage for the provision of one-third of the global water requirements (Siebert et al 2010;Famiglietti 2014). Globally, in terms of quantity and quality, groundwater resources face depletion risks impacting the viability of these resources over future decades.…”
Section: Introductionmentioning
confidence: 99%